Peningkatan Keamanan Kriptografi Caesar Cipher dengan Menerapkan Algoritma Kompresi Stout Codes - Mesran Mesran; Surya Darma Nasution (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2020)
The development of applications that can crack passwords or data that has been secured by cryptographic algorithms has made researchers try various ways to further secure the data they have. Even though the method used is quite modern, the algorithm for breaking ciphertext in cryptography can still be created. For this reason, in this study the authors develop cryptographic security by combining it with data compression. In this study, the algorithm used is the classic cryptographic algorithm, namely Caesar Cipher, combined with the Stout Codes compression algorithm. The results of the Caesar Cipher ciphertext are then compressed by applying the Stout Codes algorithm. From the test results using the Brute Force Atack model, the results are quite good, that the security of the encrypted data is quite good and not easily broken.